Agrotourism as a generator of region development - Knežević, Marija (Economics of Agriculture, 2010)
Agrotourism is a part of contemporary tourism and presents an essential factor of rural tourism in a rural environment, including all activities that occur with respect to tourism. It is based on the competitive advantage of the area, tradition, specifcity of agriculture and people. The totality of these elements makes a complete tourist product, which provides the following services to the tourists: accommodation, rest on the farm, also various specifc agricultural contents: getting the children acquainted with the farm animals, the presence during agricultural works, food production: bread, wine, brandy, food for winter, collecting medicinal herbs, tea, mushrooms, snails, as well as adventurous contents: riding, driving in horse-drawn carriages, teaching traditional crafts: production of cloth (weaving), crochet, embroidery, production of tools and similar. What is essential for an agricultural destination is its uniqueness and distinctiveness with regard to the competition. Bosnia and Herzegovina is very specifc for it offers many different contents on a geographically narrow area which can be combined into a tourist product. As it becomes more attractive tourist destination, neglected agriculture is a factor that can signifcantly support the development of tourism in the entire region.